2009
DOI: 10.1007/s00431-009-1085-y
|View full text |Cite
|
Sign up to set email alerts
|

Day 1 serum lactate values in preterm infants less than 32 weeks gestation

Abstract: Base deficit and serum lactate concentrations may be important prognostic indicators in preterm infants. We sought to (1) determine the relationship between day 1 serum lactate values and base deficit and (2) determine the relationship between day 1 biochemical parameters and adverse outcome in preterm infants <32 weeks. This was a retrospective study of all patients less than 32 weeks gestation admitted to neonatal intensive care unit over a 6-month period. All blood gases performed during the first 24 h post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…Furthermore, there is no consensus whether the sample should be drawn from the arterial, peripheral venous, or capillary blood. Most investigators found a satisfactory agreement comparing capillary or venous lactate levels with arterial levels (25)(26)(27)(28). In our opinion, such sampling should therefore be encouraged as patient undergoes this procedure with a minimal risk and inconvenience.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…Furthermore, there is no consensus whether the sample should be drawn from the arterial, peripheral venous, or capillary blood. Most investigators found a satisfactory agreement comparing capillary or venous lactate levels with arterial levels (25)(26)(27)(28). In our opinion, such sampling should therefore be encouraged as patient undergoes this procedure with a minimal risk and inconvenience.…”
Section: Discussionmentioning
confidence: 69%
“…However, the blood lactate monitoring in critically ill patient remains controversial considering the risk assessment. Some of the discrepancy is due to an uncertainty regarding the appropriate reference interval, whether to perform a single lactate measurement or serial lactate measurements as a screening method of critically ill patient (25,26,28). Furthermore, there is no consensus whether the sample should be drawn from the arterial, peripheral venous, or capillary blood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Elevated or increasing values obtained on the first day of postnatal life are associated with increased mortality in preterm and term newborns [38,39]. A single lactate value >5.6 mmol/l obtained on the first day was associated with an increased risk of adverse outcome, defined as death or severe intraventricular haemorrhage [40]. In contrast, Wardle [41] found no difference in lactate levels between normotensive and hypotensive preterm infants.…”
Section: Evaluating Systemic Perfusionmentioning
confidence: 99%